Three-decade neurological and neurocognitive follow-up of HIV-1-infected patients on best-available antiretroviral therapy in Finland. Issue 11 (5th November 2015) - Heikinheimo, T; Poutiainen, E; Salonen, O; Elovaara, I; Ristola, M
Abstract : Objectives: Is it possible to live without neurocognitive or neurological symptoms after being infected with HIV for a very long time? These study patients with decades-long HIV infection in Finland were observed in this follow-up study during three time periods: 1986–1990, in 1997 and in 2013. Setting: Patients from greater Helsinki area were selected from outpatient's unit of infectious diseases. Participants: The study included 80 HIV patients. Patients with heavy alcohol consumption, central nervous system disorder or psychiatric disease were excluded. Primary and secondary outcome measures: The patients underwent neurological and neuropsychological examinations, MRI of the brain and laboratory tests, including blood CD4 cells and plasma HIV-1 RNA. Neuropsychological examination included several measures: subtests of Wechsler Adult Intelligence Scale, Wechsler Memory Scale-Revised, list learning, Stroop and Trail-Making-B test. The Beck Depression Inventory and Fatigue Severity Scale were also carried out. The obtained data from the three time periods were compared with each other. Results: Owing to high mortality among the original 80 patients, eventually, 17 participated in all three examinations performed between 1986 and 2013. The time from the HIV diagnosis was 27 (23–30) years. Blood CD4 cells at the diagnosis were 610 (29–870) cells/mm 3, and the nadir CD4 168 (4–408) cells/mm 3 . The time on combined antiretroviral treatment was 13 (5–17) years. 9 patients suffered from fatigue, 5 had polyneuropathy and 3 had lacunar cerebral infarcts. There was a subtle increase of brain atrophy in 2 patients. Mild depressive symptoms were common. The neuropsychological follow-up showed typical age-related cognitive changes. No HIV-associated dementia features were detected. Conclusions: Polyneuropathy, fatigue and mild depression were common, but more severe neurological abnormalities were absent. These long-term surviving HIV-seropositive patients, while on best-available treatment, showed no evidence of HIV-associated neurocognitive disorder in neuropsychological and neuroradiological evaluations.